1990
DOI: 10.1111/j.1432-1033.1990.tb19435.x
|View full text |Cite
|
Sign up to set email alerts
|

A d(GpG)‐platinated decanucleotide duplex is kinked

Abstract: A conformational study of the double‐stranded decanucleotide d(GCCG*G*ATCGC) · d(GCGATCCGGC), with the G* guanines chelating a cis‐Pt(NH3)2 moiety, has been accomplished using 1H and 31P NMR, and molecular mechanics. Correlation of the NMR data with molecular models has disclosed an equilibrium between several kinked conformations and has ruled out an unkinked structure. The deformation is localized at the CG*G*· CCG trinucleotide where the helix is kinked by approximately 60° towards the major groove and unwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
97
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 47 publications
11
97
1
Order By: Relevance
“…The CP-GG and OX-GG adducts that we have studied (17, 18) (manuscript in preparation) are similar to all other Pt-GG structures reported to date in that they display an increase in roll at the G6-G7 base-pair step, G6-G7 dihedral angle and overall bend angle compared to undamaged DNA (19)(20)(21)(22)(23). We hypothesize that these common conformational features of Pt-GG adducts, which are centered around the G6-G7 base-pair step, are important for recognition of both CP-and OX-GG adducts by DNA-binding proteins.…”
Section: Dna Helical Parameters Common To All Pt-gg Adductssupporting
confidence: 50%
“…The CP-GG and OX-GG adducts that we have studied (17, 18) (manuscript in preparation) are similar to all other Pt-GG structures reported to date in that they display an increase in roll at the G6-G7 base-pair step, G6-G7 dihedral angle and overall bend angle compared to undamaged DNA (19)(20)(21)(22)(23). We hypothesize that these common conformational features of Pt-GG adducts, which are centered around the G6-G7 base-pair step, are important for recognition of both CP-and OX-GG adducts by DNA-binding proteins.…”
Section: Dna Helical Parameters Common To All Pt-gg Adductssupporting
confidence: 50%
“…Herman et al [28] have reported that in the C~S-[P~(NH,),]~+ chelate of the decanucleotide duplex d(GCCPt7GPt7GATCGC) . d(CGGCCTAGCG), the C residue complementary to the 5'G is mobile and can stack on either branch of the kinked complementary strand.…”
Section: Discussionmentioning
confidence: 99%
“…The conformational changes involved in the formation of platinated GG chelates have been elucidated recently in solution and in the crystalline state. In the X-ray structure [26] [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous crystallographic, NMR, and gel electrophoretic investigations have evaluated the impact of this crosslink on the structure and conformation of the host duplex (1)(2)(3)(4)(5)(6)(7)(8)(9). These studies indicate that formation of the cis-Pt-GG crosslink unwinds DNA by 130 and bends it by 34-55°in the direction of the major groove.…”
Section: N7(1) -N7(2)}] (Cis-pt-gg)mentioning
confidence: 99%